2009
DOI: 10.1007/s11693-009-9048-1
|View full text |Cite
|
Sign up to set email alerts
|

Internal lipid synthesis and vesicle growth as a step toward self-reproduction of the minimal cell

Abstract: One of the major properties of the semi-synthetic minimal cell, as a model for early living cells, is the ability to self-reproduce itself, and the reproduction of the boundary layer or vesicle compartment is part of this process. A minimal bio-molecular mechanism based on the activity of one single enzyme, the FAS-B (Fatty Acid Synthase) Type I enzyme from Brevibacterium ammoniagenes, is encapsulated in 1-palmitoyl-2oleoyl-sn-glycero-3-phosphatidylcholine (POPC) liposomes to control lipid synthesis. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 35 publications
(48 reference statements)
0
32
0
Order By: Relevance
“…An attempt has been recently reported that features entrapping partially purified FAS inside liposomes (Murtas 2010) in the presence of fatty acid precursors (acetyl-CoA, malonyl-CoA, NADPH). This attempt was complicated by the very large size of FAS.…”
Section: Downloaded By [University College London] At 07:47 24 June mentioning
confidence: 99%
See 1 more Smart Citation
“…An attempt has been recently reported that features entrapping partially purified FAS inside liposomes (Murtas 2010) in the presence of fatty acid precursors (acetyl-CoA, malonyl-CoA, NADPH). This attempt was complicated by the very large size of FAS.…”
Section: Downloaded By [University College London] At 07:47 24 June mentioning
confidence: 99%
“…The ENVIRONMENT platform developed by Mavelli and Ruiz-Mirazo (2007, 2010 enables stochastic simulation of vesicle systems capable of growing at the expense of externally supplied feedstock and it has been specifically designed to deal with micro-compartmentalised reactions.…”
Section: Role Of Mathematical Modelling In Synthetic Cell and Primitimentioning
confidence: 99%
“…Initial attempts in this direction have indeed been made, but with a limited success so far (Schmidli et al 1991;Kuruma et al 2009;Murtas 2010).…”
Section: Division Driven By Active Chemical Synthesis Of Materialsmentioning
confidence: 99%
“…However, this ancestor had probably no stabilizing protein-based cell wall. In the second theory, primitive cell division would proceed through a lipid biosynthesis route (Murtas 2010), in analogy to a mechanism recently observed in wall-less forms of bacteria, called L forms (Leaver et al 2009;Allan et al 2009). These L form cells are known to bypass the canonical FtsZ-centered division system and to proliferate by increased fatty acid synthesis, which leads to spontaneous cell shape deformation and scission into smaller progeny cells (Fig.…”
Section: Division Mechanisms In Early Cellsmentioning
confidence: 99%
“…Alternatively, ion channels or acyl transporters could be incorporated in the vesicle membrane to facilitate the diffusion of lipid precursors. Like phospholipid synthesis, internal production of fatty acids by fatty acid synthetases (FAS) could be considered (Murtas 2009(Murtas , 2010. A point of caution is that the high concentration of Mg 2?…”
Section: The Lipid Biosynthesis Route For Compartment Divisionmentioning
confidence: 99%